p63, a key regulator of Ago2, links to the microRNA-144 cluster - Benfan Wang; H. Helena Wu; Yasser Abuetabh; Sarah Leng; Sandra T. Davidge; Elsa R. Flores; David D. Eisenstat; Roger Leng (Cell Death and Disease, 2022)
Abstract As a key component of the RNA-induced silencing complex (RISC), Argonaute2 (Ago2) exhibits a dual function regulatory role in tumor progression. However, the mechanistic basis of differential regulation remains elusive. p63 is a homolog of the tumor suppressor p53. p63 isoforms play a critical role in tumorigenesis and metastasis. Herein, we show that p63 isoforms physically interact with and stabilize Ago2. Expression of p63 isoforms increases the levels of Ago2 protein, while depletion of p63 isoforms by shRNA decreases Ago2 protein levels. p63 strongly guides Ago2 dual functions in vitro and in vivo. Ectopic expression of the miR-144/451 cluster increases p63 protein levels; TAp63 transactivates the miR-144/451 cluster, forming a positive feedback loop. Notably, miR-144 activates p63 by directly targeting Itch, an E3 ligase of p63. Ectopic expression of miR-144 induces apoptosis in H1299 cells. miR-144 enhances TAp63 tumor suppressor function and inhibits cell invasion. Our findings uncover a novel function of p63 linking the miRNA-144 cluster and the Ago2 pathway. Facts and questions Identification of Ago2 as a p63 target. Ago2 exhibits a dual function regulatory role in tumor progression; however, the molecular mechanism of Ago2 regulation remains unknown. p63 strongly guides Ago2 dual functions in vitro and in vivo. Unraveling a novel function of p63 links the miRNA-144 cluster and the Ago2 pathway.